2001
DOI: 10.1034/j.1600-0528.2001.290601.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of selected caries prevention and management methods

Abstract: A systematic review of the periodic scientific literature was undertaken to determine the strength of the evidence for the efficacy of professional caries preventive methods applied to high risk individuals, and the efficacy of professionally applied methods to arrest or reverse non-cavitated carious lesions. An initial search identified 1435 articles, of which 27 were eventually included in the review. Among the 22 studies addressing the prevention of carious lesions in caries-active or high risk individuals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
161
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(176 citation statements)
references
References 34 publications
5
161
0
10
Order By: Relevance
“…Our results showed that the visual-tactile method failed to determine the presence of occlusal caries lesion in 3.4% of the cases, so the condition of the patient was underestimated. Concerning the application of the visual-tactile method for proximal lesions, it is generally accepted that it could lead to false negative results, especially when the process involves only the enamel [19,20]. In the diagnosis of non-cavitated proximal lesions, our results correspond to other reports: the radiographic method is accurate when the dentin is involved, but often leads to underestimation when only the enamel is affected, although it gives better results than the visual-tactile method [21,22].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Our results showed that the visual-tactile method failed to determine the presence of occlusal caries lesion in 3.4% of the cases, so the condition of the patient was underestimated. Concerning the application of the visual-tactile method for proximal lesions, it is generally accepted that it could lead to false negative results, especially when the process involves only the enamel [19,20]. In the diagnosis of non-cavitated proximal lesions, our results correspond to other reports: the radiographic method is accurate when the dentin is involved, but often leads to underestimation when only the enamel is affected, although it gives better results than the visual-tactile method [21,22].…”
Section: Resultssupporting
confidence: 78%
“…False positive results were measured. Other authors obtained similar results, too [16,17,19,20]. Based on these and our study, we could recommend the device to be used as an adjunct method.…”
Section: Resultssupporting
confidence: 74%
“…According to some of the results, the radiographic method was found to have worse performance than the visual examination and LF device methods when compared using sensitivity, specificity, accuracy, and AUC values (20)(21)(22)(23). This could be due to the depth of the caries lesion on the radiograph, difficulty in noticing hidden caries because of the fissure system and not removing all of the colorization on the occlusal region (21,24,25). Therefore, new methods are being researched for early caries lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the difficulties in diagnosing borderline cases (i.e., H-Ts may have less experience in screening for caries). This would appear reasonable given the difficulties in caries diagnosis at all levels of the profession (Bader et al 2001) and the proliferation of adjunctive aids to inform this decision. The forest plots ( Figs.…”
Section: Discussionmentioning
confidence: 99%